KARDIOCHIRURGIA DOROSŁYCHSecondary mitral regurgitation annuloplasty in patients with congestive cardiomyopathy – own experience - Sadowski, Jerzy; Wójcik, Sławomir; Wierzbicki, Karol; Piątek, Jacek; Milaniak, Irena; Przybyłowski, Piotr; Sobczyk, Dorota; Górkiewicz-Kot, Izabella; Drwiła, Rafał; Klimeczek, Piotr; Wróbel, Krzysztof; Pasowicz, Mieczysław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Introduction: In the pathophysiology of heart failure in the ourse of congestive cardiomyopathy, secondary mitral regurgitation (SMR) plays an important role. SMR intensifies left ventricular enlargement and causes additional decrease of minute cardiac volume. Mitral annuloplasty can be an effective method of surgical management in this group of patients. Aim of the study: To evaluate the efficiency of undersized mitral annuloplasty in patients with advanced congestive cardiomyopathy and concomitant SMR using classical and new (cardiac magnetic resonance) diagnostic methods. Methods and study population: The analysis included 17 patients (3 F, 14 M aged 24-61 years, average 51.1±9.3 years) with congestive cardiomyopathy and concomitant SMR. Prospective evaluation of the study subgroup was performed during one year following the operation. Results: Immediately after the operation in all of the patients TEE showed efficiency of the procedure. One patient died because of rapid heart failure exacerbation and secondary multiple organ dysfunction, after the operation. During the follow-up period significant improvement of NYHA class was observed; only 3 patients had progression of heart failure (NYHA class). CMR revealed regression in the early period, then again progression of left ventricular volume despite the regression of mitral regurgitation. Conclusion: Undersized mitral annuloplasty in patients with congestive cardiomyopathy and SMR may bring functional improvement in the subgroup with careful qualification for the procedure. Despite that, in some patients during the follow-up period, exacerbation of heart failure and progressive left ventricular enlargement (observed in CMR) occur.